Methoprene (Altosid) ® larvicide's activity determination on vector mosquitoes in a high transmission area - Castro, Julia (2007)
Objectives: To determine growth regulating hormone methoprene larvicide's activity. Design: Experimental study. Setting: Instituto de Investigacion de Ciencias Biologicas Antonio Raimondi, Facultad de Ciencias Biologicas, Universidad Nacional Mayor de San Marcos. Sub-Region de Salud de Madre de Dios. Centro de Investigacion Biologica para el Desarrollo Amazonico. Biologic material: Stages III and IV Aedes aegypti larves. Interventions: Three laboratory bioessays were done to determine regulating hormone methoprene (Altosid)® on 7 000 stages III and IV Aedes aegypti larves, in the laboratory and in Anopheles benarrochi natural breeding places. Larval population was obtained from breeding places located in La Cachuela, La Joya and Las Piedras communities, Tambopata province (Puerto Maldonado), Madre de Dios department. Larvicide activity was determined by 2 methoprene doses, 0,004 and 0,008 g/L. Bioessays were done by triplicate using breeding places water. Readings at 24, 48, 72 and 96 hours following treatment were done to determine both efficacy and susceptibility. Main outcome measures: Methoprene larvicide activity. Results: Mortality of 85,2% and 92% was obtained for 0,004 and 0,008 g/L dilutions, both at the laboratory and natural breeding places. Median lethal doses (LD50) were 0,0018, 0,0014, 0,0017 and 0,0012 g/L, at 24, 48, 72 y 96 hours respectively. Application on breeding places was done with 0,008 g/L methoprene dosis obtaining 0,0056, 0,0048, 0,0034 and 0,0025 g/L LD50 at 24, 48, 72 y 96 hours, respectively. LD90 was 0,0098, 0,0086 g/L, 0,008 g/L and 0,0070 g/L, at 24, 48, 72 and 96 hours respectively, obtaining 100% mortality at 96 hours. Conclusions: Maximum effectiveness was obtained with methoprene 0,008 g/L dose at 96 hours.